The value of prenatal magnetic resonance imaging and postnatal follow-up using Gesell Developmental Schedules score for mild-to-moderate simple bilateral fetal ventriculomegaly. (12th December 2022) - Li, Zhi; Pan, Liming; Chen, Yaning; Meng, Diyun; Liu, Yuqin; Li, Lan; Liu, Mingsong; Luo, Zhiqin
Abstract: Objective: To investigate the relationship of mild-to-moderate simple bilateral fetal ventriculomegaly with postnatal neurological development. Methods: Cases of simple lateral ventricular dilatation (273) were divided into bilateral mild dilatation (10.0–12.0 mm, 62), bilateral moderate dilatation (12.1–15.0 mm, 29), unilateral mild dilatation (133), and unilateral moderate dilatation (49) groups. The control group comprised 50 normal fetuses. Neurological development was assessed using Gesell Developmental Schedules (GDS) at postnatal 3, 6, 12, and 18 months. Results: At postnatal 6, 12, and 18 months, the GDS score was higher for bilateral than for unilateral dilatation ( p < .05). At postnatal 3 and 6 months, the GDS score was higher for the bilateral dilatation groups than for the control group ( p < .05). At postnatal 6, 12, and 18 months, the GDS score was higher for the bilateral moderate dilatation group than for the unilateral moderate dilatation group ( p < .05). Further, at postnatal 3, 6, 12, and 18 months, the GDS score was higher for the bilateral moderate dilatation group than for the control group ( p < .05). Conclusion: At postnatal month 6, the GDS evaluation results of the bilateral dilatation groups were significantly inferior compared to those of the unilateral dilatation group.